Analysis of the Justice Component of a JEDI (Justice, Equity, Diversity, and Inclusion) Inventory in a College of Pharmacy - Chad W. Schulz; Jackson J. Dubas; Allison M. Dering-Anderson; Karen L. Hoff; Adam L. Roskam; Noah A. Kasbohm; Brady W. Holtmeier; Hannah L. Hansen; Kaitlyn L. Stukenholtz; Ashley N. Carron; Lindsey M. Tjards (MDPI AG, 2024)
At the University of Nebraska Medical Center College of Pharmacy, a longitudinal project is underway to assess how the college is functioning in terms of keeping Justice, Equity, Diversity, and Inclusion (JEDI) at the forefront of the institution. This study is intended to showcase areas of excellence within the college and as a quality improvement exercise to show the institution potential areas in need of improvement. This process was also initiated because such assessments may soon become a requirement for colleges of pharmacy to earn full accreditation. Upon analyzing the Justice component of JEDI and the 32 justice-related ideas that were recommended for exploration and discussion, and further sub-categorized under the terms representation, curriculum and education, policies and procedures, support and resources, and college climate, useful data were discovered. Overall, the information found on representation, policy and procedure, and college climate was difficult to quantify as much of the information was subjective; however, this does not automatically discount this information from being useful. Information relating to curriculum and education was more quantifiable but may be underrepresented. Analyzing information found relating to resources was made possible by identifying readily available support offered at the college for faculty, staff, and students. In identifying these resources, the college was able to take note of any missing support that needed to be implemented to ensure justice was being maintained. This longitudinal process not only allows the college to see areas where they thrive, but it also highlights any shortcomings of the college while providing the institution with information to spark innovative ideas to strengthen and further promote justice.